A Randomized Trial of Continuous Noninvasive Blood Pressure Monitoring During Noncardiac Surgery. (August 2018) - Maheshwari, Kamal; Khanna, Sandeep; Bajracharya, Gausan Ratna; Makarova, Natalya; Riter, Quinton; Raza, Syed; Cywinski, Jacek B.; Argalious, Maged; Kurz, Andrea; Sessler, Daniel I.
Abstract : BACKGROUND: Intraoperative hypotension is associated with postoperative mortality. Early detection of hypotension by continuous hemodynamic monitoring might prompt timely therapy, thereby reducing intraoperative hypotension. We tested the hypothesis that continuous noninvasive blood pressure monitoring reduces intraoperative hypotension. METHODS: Patients ≥45 years old with American Society of Anesthesiologists physical status III or IV having moderate-to-high-risk noncardiac surgery with general anesthesia were included. All participating patients had continuous noninvasive hemodynamic monitoring using a finger cuff (ClearSight, Edwards Lifesciences, Irvine, CA) and a standard oscillometric cuff. In half the patients, randomly assigned, clinicians were blinded to the continuous values, whereas the others (unblinded) had access to continuous blood pressure readings. Continuous pressures in both groups were used for analysis. Time-weighted average for mean arterial pressure <65 mm Hg was compared using 2-sample Wilcoxon rank-sum tests and Hodges Lehmann estimation of location shift with corresponding asymptotic 95% CI. RESULTS: Among 320 randomized patients, 316 were included in the intention-to-treat analysis. With 158 patients in each group, those assigned to continuous blood pressure monitoring had significantly lower time-weighted average mean arterial pressure <65 mm Hg, 0.05 [0.00, 0.22] mm Hg, versus intermittent blood pressure monitoring, 0.11 [0.00, 0.54] mm Hg ( P = .039, significance criteria P < .048). CONCLUSIONS: Continuous noninvasive hemodynamic monitoring nearly halved the amount of intraoperative hypotension. Hypotension reduction with continuous monitoring, while statistically significant, is currently of uncertain clinical importance.